Managing to Adapt: Analysing adaptive management for planning, monitoring, evaluation, and learning - Desai, Harsh; Maneo, Gabriele; Pellfolk, Erica; Schlingheider, Annika (Oxfam Research Reports, 2018)
Adaptive management is at the heart of ‘Doing Development Differently’. It emerges from stakeholders’ calls for development programmes to be more flexible and responsive to their contexts. Whether it becomes a mainstreamed practice depends on how much it is

Adaptive Management Tools: Concept Notes System - Mercy Corps (Mercy Corps, 2015)
Mercy Corps finds adaptive management is supported by four different but interconnected elements: Culture, People & Skills, Tools & Systems, and Enabling Environment. These elements are discussed in the context of one of Mercy Corps’ complex programmes in pastoral Ethiopia.

Toybox's Adaptive Management in Practice - Malcolm, Emily (Toybox, 2017)
At Toybox, we understand ‘Adaptive Management’ as a broad innovative and learning approach that involves the whole organisation, our partners and funders. ‘Adaptive Programming’ of projects is part of this approach which is greatly enhanced by the Adaptive Management of all actors, including communities and children in the projects. Over the last few years Toybox have been piloting Adaptive Programming with our partners across Latin America, Africa and Asia to support children in street situations. This project has been developed within the wider context of an organisation which is focused on innovation and learning, therefore enabling Adaptive Management to become mainstream within the organisation. This paper captures the experiences and learnings of Toybox to our newly implemented Adaptive Programming approach, through the lens of a small-sized UK-based organisation working with local organisations internationally. This paper explains our learnings, inclusive of why we believe Adaptive Management is important to Toybox and how the organisation has embraced this new approach.

Doing Development Differently at Scale - Pellini, Arnaldo; Karetji, Petrarca C.; Soekadis, Ade (Knowledge, Politics and Policymaking in Indonesia, 2018)
In recent decades there has been an increasing recognition that politics and political institutions matter for development. There is also a much greater interest in contextually grounded approaches. This has stemmed from an acknowledgement that purely technocratic approaches to development often result in failure because they do not take into account the nature of political institutions. Nor do they take account of the context in a particular developing country and the interests and incentives of powerful national actors. Policy processes are embedded in specific social, political and organisational contexts. Approaches that focus on implementing universal best practices in evidence-informed policymaking are unlikely to be successful. Instead, what is needed is an approach that takes the local context as the starting point for understanding what issues are relevant to policymakers and developing contextually appropriate solutions. The authors of this chapter reflect on the management approaches and systems that may be required to enable and support large-scale development programmes to be flexible and adaptive to the local policy context and circumstances. The chapter argues that such programmes struggle to adopt adaptive management principle and that to do that at scale requires some changes in the way such programmes are managed.
Keywords: Adaptive Management; Doing development differently; Evidence-informed policymaking; Indonesia; Knowledge sector; Thinking and working politically

Monitoring, Evaluation and Learning in NGO Advocacy - Findings from Comparative Policy Advocacy MEL Review Project - Coe, Jim; Majot, Juliette (ODI and Oxfam, 2013)
For organizations committed to social change, advocacy often figures as a crucial strategic element. How to assess effectiveness in advocacy is, therefore, important. The usefulness of Monitoring, Evaluation and Learning (MEL) in advocacy are subject to much current debate. Advocacy staff, MEL professionals, senior managers, the funding community, and stakeholders of all kinds are searching for ways to improve practices – and thus their odds of success – in complex and contested advocacy environments. This study considers what a selection of leading advocacy organizations are doing in practice. We set out to identify existing practice and emergent trends in advocacy-related MEL practice, to explore current challenges and innovations. The study presents perceptions of how MEL contributes to advocacy effectiveness, and reviews the resources and structures dedicated to MEL.

Valuing peace: delivering and demonstrating mediation results - Dilemmas & options for mediators - Wadley, Ian (Mediation Practice Series, 2017)
Essential points for practitioners and donors • Mediation offers a cost-effective and proven method for resolving armed conflict. Between 1985 and 2015, 75 per cent of armed conflicts in the world were resolved through agreement rather than by force. In most cases these processes will have involved third party facilitation or support. • Professional mediators understand the high stakes involved in their work to prevent, mitigate and resolve armed conflict. In addition, they and their financial supporters are increasingly required to demonstrate ‘value-for-money’ to ensure continued funding. • However, traditional monitoring and evaluation (M&E) methods are not well suited to this task, typically imposing artificially linear project models on a dynamic conflict situation, as well as compliance reporting that moves attention away from real value. • Traditional M&E methods tend to focus on documenting the past and generating vast amounts of data, rather than enabling timely adaptation of the project in the present. • Traditional M&E approaches rely heavily on external evaluation consultants. Even in the best of cases this may interfere with the mediation process and impose a heavy time burden on the project team, leading to low acceptance of traditional M&E approaches by mediation practitioners. • In contrast, an ideal M&E approach for mediation should deliver useful insights in even the most dynamic and sensitive mediation environments, impose a light reporting burden, and be readily accepted by mediation teams. It should protect discretion and trust, enable rapid adaptation, and also provide some assurance that donor funds are being well spent.

Making humanitarian response more flexible: Challenges and questions - Obrecht, Alice; Bourne, S. (ALNAP/ODI, 2018)

Doing Development Differently in the Global South - Workshop Report - CARE (CARE and British Council, 2018)

Failing Forward: How CARE is focusing on what goes wrong to improve impact - Janoch, Emily (2019 CLA Case Competition, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs. It's also allowing us to make connections across a global portfolio of more than 900 projects, and with new and different partners to learn from their experience.

What can the Thinking and Working Politically community learn from peace and conflict mediation? - Douglas, Alex (From Poverty to Power, 2018)
Wily aid practitioners have long understood the importance of adapting their programs to the political environment, and even use their activities to push politics in a progressive direction. But this magic was spun secretly, hidden behind logframes and results frameworks. Only recently has a range of programs been permitted to escape the dead hand of technocracy. But there was one corner of the development and humanitarian world that never needed to shroud its political ambitions; those of us working on resolving violent conflicts. Donors have always understood our work could never be disembodied from politics. This field included elements of the UN, regional organisations, and NGOs, such as the one I work for: the Centre for Humanitarian Dialogue. With a new focus on development being enabled by a series of ‘deals’ between different actors, it seems timely to examine the strategies used to reach peace agreements and whether they contain broader lessons for TWP/DDD/Adaptive Management.

NGOs Doing Development Differently - Green, Duncan (From Poverty to Power, 2017)
Report back from a meeting of international NGOs to set up a research and practice network on 'Doing Development Differently' that can complement other actors